2015
DOI: 10.1039/c4dt03233k
|View full text |Cite
|
Sign up to set email alerts
|

Ionothermal synthesis and crystal structures of novel aluminum phosphates with in situ generated templates

Abstract: Protic ionic liquids (PILs) are a subgroup of ionic liquids and easily formed by proton transfer from a Brønsted acid to a Brønsted base. Two new crystalline aluminophosphates, [C5H16N2][Al(PO4)(HPO4)] (AlPO-PIL1) and [C5H16N2][Al2(OH)2 (PO4)2] (AlPO-PIL2), are successfully prepared for the first time from a protic ionic liquid, 3-dimethylaminopropylamine acetate. Their structures were determined from single-crystal X-ray diffraction data. It was found that HF in the reaction mixture is crucial in determining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Ge et al demonstrated a versatile ionothermal strategy to synthesize a series of nanostructured nickel compounds, including Ni(NH 3 ) 6 Cl 2 crystals, NiCl 2 nanosheets, α‐Ni(OH) 2 nanoflowers, and mesoporous NiO nanoflowers . Man et al synthesized novel aluminum phosphates in a protic IL …”
Section: Ils Used As Synthetic Mediamentioning
confidence: 99%
“…Ge et al demonstrated a versatile ionothermal strategy to synthesize a series of nanostructured nickel compounds, including Ni(NH 3 ) 6 Cl 2 crystals, NiCl 2 nanosheets, α‐Ni(OH) 2 nanoflowers, and mesoporous NiO nanoflowers . Man et al synthesized novel aluminum phosphates in a protic IL …”
Section: Ils Used As Synthetic Mediamentioning
confidence: 99%